Which clinical markers for appropriate timing of surfactant therapy? - Lista, G.; Castoldi, F. (Acta Biomedica Atenei Parmensis, 2013)
Preterm infants with RDS need adequate resuscitation maneuvers and appropriate timing of surfactant replacement but about the latter there is not an universal consensus. A correct evaluation should consider at the same time the administration of antenatal steroids, the radiological criteria, the clinical presentation, the FiO2 level, OI and a/ApO2.